Trehalose-6-phosphate promotes fermentation and glucose repression in Saccharomyces cerevisiae - Rebeca L. Vicente; Lucie Spina; Jose P.L. Gómez; Sebastien Dejean; Jean-Luc Parrou; Jean Marie François (Microbial Cell, 2018)
The yeast trehalose-6-phosphate synthase (Tps1) catalyzes the formation of trehalose-6-phosphate (T6P) in trehalose synthesis. Besides, Tps1 plays a key role in carbon and energy homeostasis in this microbial cell, as shown by the well documented loss of ATP and hyper accumulation of sugar phosphates in response to glucose addition in a mutant defective in this protein. The inability of a Saccharomyces cerevisiae tps1 mutant to cope with fermentable sugars is still a matter of debate. We reexamined this question through a quantitative analysis of the capability of TPS1 homologues from different origins to complement phenotypic defects of this mutant. Our results allowed to classify this complementation in three groups. A first group enclosed TPS1 of Klyveromyces lactis with that of S. cerevisiae as their expression in Sctps1 cells fully recovered wild type metabolic patterns and fermentation capacity in response to glucose. At the opposite was the group with TPS1 homologues from the bacteria Escherichia coli and Ralstonia solanacearum, the plant Arabidopsis thaliana and the insect Drosophila melanogaster whose metabolic profiles were comparable to those of a tps1 mutant, notably with almost no accumulation of T6P, strong impairment of ATP recovery and potent reduction of fermentation capacity, albeit these homologous genes were able to rescue growth of Sctps1 on glucose. In between was a group consisting of TPS1 homologues from other yeast species and filamentous fungi characterized by 5 to 10 times lower accumulation of T6P, a weaker recovery of ATP and a 3-times lower fermentation capacity than wild type. Finally, we found that glucose repression of gluconeogenic genes was strongly dependent on T6P. Altogether, our results suggest that the TPS protein is indispensable for growth on fermentable sugars, and points to a critical role of T6P as a sensing molecule that promotes sugar fermentation and glucose repression..